Optimization Of Power And Gain In Two-Stage Op-amp By Using Taguchi's Approach - Mohd Chachuli, Siti Amaniah; Arith, Faiz; Idris, Muhammad Idzdihar (Trans Tech Publications Ltd, 2013)
This paper presents a method based on statistical approach which known as Taguchi method. This method is used to optimize power dissipations and gain in a two-stage op-amp. Standard L27 which uses three factors and two outputs is chosen to optimize power and gain in the circuit.Simulation of the circuit has been implemented by using Mentor Graphics DA-IC. From the simulation, the results showed that total power dissipation has decreased from 3.9643 mW to 1.0345 mW. The percentage of power reduction is 73.9%. The overall gain also has been improved from 22 dB to 45.49 dB. The percentage of increment gain in two-stage op-amp is 56%.